A Lactobacillus mutant capable of accumulating long-chain polyphosphates that enhance intestinal barrier function*. Issue 5 (3rd May 2016) - Saiki, Asako; Ishida, Yasuaki; Segawa, Shuichi; Hirota, Ryuichi; Nakamura, Takeshi; Kuroda, Akio
Abstract : Inorganic polyphosphate (polyP) was previously identified as a probiotic-derived substance that enhances intestinal barrier function. PolyP-accumulating bacteria are expected to have beneficial effects on the human gastrointestinal tract. In this study, we selected Lactobacillus paracasei JCM 1163 as a strain with the potential to accumulate polyP, because among the probiotic bacteria stored in our laboratory, it had the largest amount of polyP. The chain length of polyP accumulated in L . paracasei JCM 1163 was approximately 700 phosphate (Pi) residues. L . paracasei JCM 1163 accumulated polyP when Pi was added to Pi-starved cells. We further improved the ability of L . paracasei JCM 1163 to accumulate polyP by nitrosoguanidine mutagenesis. The mutant accumulated polyP at a level of 1500 nmol/mg protein—approximately 190 times that of the wild-type strain. PolyP extracted from the L . paracasei JCM 1163 significantly suppressed the oxidant-induced intestinal permeability in mouse small intestine. In conclusion, we have succeeded in breeding the polyP-accumulating Lactobacillus mutant that is expected to enhance intestinal barrier function. Graphical abstract: Time course of polyP production and overplus induction in L . paracasei JCM 1163